The Effect of Nutritional Knowledge Levels of Hemodialysis Patients on Nutritional Status - Yakar, Burkay; Demir, Mustafa; Canpolat, Omer (Duzce Univ, 2019)
Objective: Nutritional disorders in hemodialysis patients are among the most important determinants of mortality and morbidity. It is known that one of the most effective ways of ensuring the adaptation of hemodialysis patients to their diets and protecting them from malnutrition is to increase the knowledge level of patients about nutrition. In our study, it was aimed to investigate the effect of nutritional information level on the nutritional status of hemodialysis patients. Methods: The population of our cross-sectional study was composed of patients followed in the dialysis unit of a university hospital. The data were obtained by Mini Nutritional Assessment Questionnaire, Nutrition Knowledge Level Questionnaire and Sociodemographic Questionnaire. Chi-square test was used in the analysis of categorical data. Student's t-test was used to compare two independent groups for normal distributed data. Data were evaluated with a 95% confidence interval and p<0.05 was considered statistically significant. Results: The average age of 109 participants was 52.76 +/- 14.14. 20.2% of the participants had malnutrition, 32.1% had malnutrition and 47.7% had no malnutrition risk. As the educational level (p = 0.01) and nutritional information score increased (p < 0.001), it was seen that the malnutrition decreased while It was seen that malnutrition increased with increasing hemodialysis period (p = 0.03). Conclusions: The fact that the nutritional disorders of the participants were related to educational level and nutritional knowledge levels suggested that nutritional disorders could be reduced by increasing the knowledge level of hemodialysis patients.
Keywords: Hemodialysis; Malnutrition; Level of Knowledge